SISTEM PAKAR DIAGNOSA POST TRAUMATIC STRESS DISORDER DENGAN METODE FORWARD CHAINING - Mochamad Rizky Zaldi; Seng Hansun (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2024)
Post traumatic stress disorder (PTSD) is a disorder experienced by someone due to surprising, scary, or dangerous events they had. Unfortunately, there is minimal knowledge about this disorder among Indonesian people so that many of them do not know what symptoms they have experienced and the effects from the disorder. The aim of this study is to build an expert system for early diagnose of this PTSD. Forward chaining method is utilized within the expert system to collect the symptoms experienced by users, processing them based on knowledge rules until a decision or conclusion achieved. The expert system was developed following the Expert System Development Life Cycle (ESDLC) and the built system usability level was measured by using the USE questionnaire. The system was then tested together with an expert that showed the agreement level of the system with the expert. From the Usability level measurement, the system got a score of 86.67% which show the system is useful for early diagnose of PTSD. Hopefully, this expert system could become a solution in giving ease of accessibility for people to get an early diagnose result of PTSD.